Qualitative fitting characteristics of filtering face-piece respirators on Iranian people - Fakherpour, Anahita; Jahangiri, Mehdi; Seif, Mozhgan (Journal of environmental health science and engineering, 2020)
To evaluate the qualitative fitting characteristics of FFRs on Iranian people. 62 participants were fit tested qualitatively by four brands of FFRs, including three imported (A, B, and C) and one domestic (D). The respirators were assigned to the participants randomly based on the Latin Square design (LSD) using the Moldex® Bitrex® Fit Test Kit. R 3.2.5.0 software was used to analyze the data. Among the respirators, A and C respirators had the lowest and highest fit test passing rates with 1.60% and 43.50%, respectively. The majority of the participants had medium face sizes (45.20%) and small and long/narrow shapes (32.20% and 32.30%). There was a significant difference between the passing rate of domestic (D) and imported (C) respirators ( p value<0.001). Factors including respirator brand, style, and gender had significant effects on respirator fit (p value<0.01). There was a low fit test passing rate of the studied respirators among participants. Furthermore, 19.40% of the participants fell out of the NIOSH fit test panel. Therefore, it is required to develop a unique bivariate fit test panel and design the respirators based on the Iranian facial dimensions. Meantime, manufacturers need to provide various sizes and styles of the respirators to provide adequate respiratory protection for the users.